1994
DOI: 10.1128/jb.176.21.6590-6598.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, DNA sequencing, and characterization of a nifD-homologous gene from the archaeon Methanosarcina barkeri 227 which resembles nifD1 from the eubacterium Clostridium pasteurianum

Abstract: (Res. Microbiol. 142:5-12, 1991)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 45 publications
8
84
0
Order By: Relevance
“…Additional open reading frames in the adjacent regions on either side of the cluster have been tentatively identified as a flavine-containing oxidoreductase (upstream of nifH) and a periplasmic molybdate binding protein plus a molybdenum transporter (downstream of nifN). The order of the M. mazei nitrogen fixation genes is the same as in other diazotrophic methanogenic archaea and differs from most bacterial nif gene clusters in that the two nifI genes are located between nifH and nifD (Sibold et al 1991, Chien and Zinder 1994, Kessler et al 1998, Arcondeguy et al 2001. Phylogenetic analysis of the deduced amino acid sequence of the M. mazei Gö1 nif genes showed that they are most closely related to M. barkeri nif2 genes, suggesting that M. mazei Gö1 has a molybdenum-containing nitrogenase (Table 1).…”
Section: Sequencing and Nucleotide Analysis Of The Nif Gene Cluster Fmentioning
confidence: 93%
See 1 more Smart Citation
“…Additional open reading frames in the adjacent regions on either side of the cluster have been tentatively identified as a flavine-containing oxidoreductase (upstream of nifH) and a periplasmic molybdate binding protein plus a molybdenum transporter (downstream of nifN). The order of the M. mazei nitrogen fixation genes is the same as in other diazotrophic methanogenic archaea and differs from most bacterial nif gene clusters in that the two nifI genes are located between nifH and nifD (Sibold et al 1991, Chien and Zinder 1994, Kessler et al 1998, Arcondeguy et al 2001. Phylogenetic analysis of the deduced amino acid sequence of the M. mazei Gö1 nif genes showed that they are most closely related to M. barkeri nif2 genes, suggesting that M. mazei Gö1 has a molybdenum-containing nitrogenase (Table 1).…”
Section: Sequencing and Nucleotide Analysis Of The Nif Gene Cluster Fmentioning
confidence: 93%
“…As with bacterial nitrogen fixation, nif gene transcription in methanogenic archaea is regulated by the availability of nitrogen (Souillard and Sibold 1989, Chien and Zinder 1994, Kessler et al 1998. However, because of the major differences between archaeal and bacterial transcription, it is likely that the mechanisms of methanogenic nif gene regulation differ significantly from bacterial nif regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Specialized characteristics such as those producing insect-toxic protein crystals or dinitrogen fixation give the appearance of having moved from genome to genome horizontally (Chien and Zinder, 1994;Galibert et al, 2001). Other, less obvious, features, no doubt have moved also.…”
Section: Horizontal Gene Transfer and Its Effect On Evolution Of Bactmentioning
confidence: 99%
“…Other examples of features that appear across a wide range of genera considered distantly related by some measures, but which might be closely related by other criteria, include complex metabolic functions important to biotechnology exemplified by the nitrogenase complex genes or aromatic biodegradation genes (Chien and Zinder 1994;Hirsch et al, 1995;Harwood and Parales, 1996). How this may happen may be explained by recent developments in genomics, which is the study of an organism's genetic material.…”
Section: Use Of Taxonomy As a Basis For Further Inquiriesmentioning
confidence: 99%
“…In these analyses (26,38), there were four major branches. Three branches contained nifH genes that function in nitrogen fixation, while the fourth branch contained genes that evidently participate in a process unrelated to nitrogen fixation.…”
Section: Evolution Of Nitrogen Fixationmentioning
confidence: 99%